Prone Position in Percutaneous Nephrolithotomy and Postoperative Visual Loss - Agah, Mahvash; Ghasemi, Mahshid; Roodneshin, Fatemeh; Radpay, Badiozaman; Moradian, Siamak (Urology Journal, 2011)
Purpose: To study the simultaneous effects of prone position and anesthesia on intraocular pressure (IOP) and the time impact on post anesthesia visual loss development in percutaneous nephrolithotomy (PCNL). Materials and Methods: Twenty patients who were candidates for PCNL were recruited in this study. Intraocular pressure was measured in five occasions: 1. Base line; 2. Ten minutes after anesthesia (Supine-I); 3. Ten minutes after position change to prone (Prone-I); 4. At the end of the operation (Prone-II); and 5. Ten minutes after position change to supine (Supine-II). The data were analyzed by SPSS software using repeated measures ANOVA and paired t test. Results: The participants consisted of 17 (85%) men and 3 (15%) women, with the mean age of 44 years. The duration of the prone position was 79.75 ± 22.73 minutes. Intraocular pressure changed significantly in five positions (P = .000). It was lower in supine-I than baseline, higher in prone-I than base line and supine-I, lower in supine-II than prone-II, and highest in prone-II (P = .000). There was a linear relationship between IOP and prone position duration (r = 0.67; P = .001). Conclusion: Intraocular pressure dropped significantly after anesthesia and increased in prone position. There was a linear relationship between IOP rise and the prone position duration, doubled within two hours. Therefore, in PCNL carried out in prone position, it is recommended to observe safety measures and necessary precautions for IOP rise and possible post anesthesia visual loss, particularly in glaucoma.